Processing of burnt molding earth - Zalyhina, Volha S.; Cheprasova, Victoria I.; Novitskaya, Daria P. (Journal of the Belarusian State University. Ecology, 2022)
At present, the metallurgical industry occupies one of the leading positions in the economy of many countries. At the same time, a large amount of solid wastes is generated in the metallurgical industry. The most large-tonnage includes burnt molding earth, which is formed at the stage of knocking out castings from foundry molds. The properties of burnt molding earth (humidity, loss on ignition, elemental, phase and grain composition) were studied and the possibility of its regeneration was confirmed. The simplest and cheapest is the dry mechanical method of regeneration, which is used in most enterprises of the Republic of Belarus. The paper shows that when this method is implemented, about 80 % of the burnt molding earth is returned to the technological process at the stage of casting molds, and about 20 % is converted into a fine pulverized fraction, which is a waste product and is currently being disposed of for disposal.On the basis of experimental studies, it has been established that this fraction of burnt molding earth can be used in the production of ceramic bricks as a lean additive. Were obtained samples of ceramic bricks containing 80 wt. % clay field «Lukoml», as well as sand and a fine fraction of the molding burnt earth in various proportions. The properties of the obtained samples, their structure and phase composition have been studied. It has been established that with an increase in the content of waste, the properties of ceramic bricks change insignificantly. Therefore, it is proposed to use 20 wt. % of the finely dispersed fraction of the burnt molding earth, i.e., completely replace the quartz sand with waste. On the basis of experimental studies, firing at a temperature of 1000 °C with isothermal holding for 60 minutes was chosen. It has been established that the obtained samples of ceramic bricks correspond to GOST 530-2012 «Ceramic brick and stone. General Specifications», stamp 300.
Keywords: waste; burnt molding earth; foundry production; fine fraction; water absorption; compressive strength